ПРАВОВОЕ РЕГУЛИРОВАНИЕ ДОГОВОРА БАНКОВСКОГО КРЕДИТА - Арсени, Игорь (SUPREMANCE OF LAW, 2019)
In this article, the author reveals the features of the legal regulation of a bank loan, highlights its main elements, as well as its place in the system of civil law contracts. In particular, the author separately studied the legal framework and the economic essence of a bank loan agreement.
Keywords: bank loan agreement; banks; non-banking institutions; loan